EDUCATION QUALITY MANAGEMENT BASED ON MONITORING STUDIES - Yevgeny V. Borzov; Irina I. Koryagina; Olga I. Votyakova; Natalya V. Kurileva (Образование и наука)
The purpose of the research is to justify a systematic approach to education quality management based on monitoring studies.Methods. A set of complementary methods based on the principles of scientific methodology is used: theoretical – analysis, synthesis, generalization of scientific and methodical work in accordance with the stated theme; methods of empirical research – questionnaires, surveys, interviews, participant observation with the following collection, storage and statistical data processing.Results and scientific novelty. The complete ordered system of criteria and indicators of quality of activities of educational institution is created. The complex of the following monitoring procedures is developed: the survey of students and their parents at the completion of the module; the graduates questionnaire; students semester interviewing; analysis of the graduates employment, collecting applications from the employers for graduates of the present areas of training, annual survey of employers.Practical significance. It is shown that the tried and tested system of monitoring serves as the measuring tool allowing to signal timely about possible failures in educational process at the different levels, providing steady functioning of higher education institution as difficult structure according to the set parameters, in the optimum mode and with preserving quality of educational services.